The Circadian PER2 Enhancer Nobiletin Reverses the Deleterious Effects of Midazolam in Myocardial Ischemia and Reperfusion Injury - Oyama, Yoshimasa; Bartman, Colleen M.; Gile, Jennifer; Sehrt, Daniel; Eckle, Tobias (Current Pharmaceutical Design, 2018)
Background: Recently, we identified the circadian rhythm protein Period 2 (PER2) in robust cardioprotection from myocardial ischemia (MI). Based on findings that perioperative MI is the most common major cardiovascular complication and that anesthetics can alter the expression of PER2, we hypothesized that an anesthesia mediated downregulation of PER2 could be detrimental if myocardial ischemia and reperfusion (IR) would occur. Methods and Results: We exposed mice to pentobarbital, fentanyl, ketamine, propofol, midazolam or isoflurane and determined cardiac Per2 mRNA levels. Unexpectedly, only midazolam treatment resulted in an immediate and significant downregulation of Per2 transcript levels. Subsequent studies in mice pretreated with midazolam using an in-situ mouse model for myocardial (IR)-injury revealed a significant and dramatic increase in infarct sizes or Troponin-I serum levels in the midazolam treated group when compared to controls. Using the recently identified flavonoid, nobiletin, as a PER2 enhancer completely abolished the deleterious effects of midazolam during myocardial IR-injury. Moreover, nobiletin treatment alone significantly reduced infarct sizes or Troponin I levels in wildtype but not in Per2-/- mice. Pharmacological studies on nobiletin like flavonoids revealed that only nobiletin and tangeritin, both found to enhance PER2, were cardioprotective in our murine model for myocardial IR-injury. Conclusion: We identified midazolam mediated downregulation of cardiac PER2 as an underlying mechanism for a deleterious effect of midazolam pretreatment in myocardial IR-injury. These findings highlight PER2 as a cardioprotective mechanism and suggest the PER2 enhancers nobiletin or tangeritin as a preventative therapy for myocardial IR-injury in the perioperative setting where midazolam pretreatment occurs frequently.
Keywords: perioperative myocardial ischemia